Chappie - Blomkamp, Neill, 1979-; Tatchell, Terri; Kinberg, Simon; Waisbren, Benjamin; Copley, Sharlto, 1973-; Patel, Dev, 1990-; Ninja; Visser, Yolandi, 1984-; Cantillo, Jose Pablo, 1979-; Auret, Brandon; Weaver, Sigourney, 1949-; Jackman, Hugh; et al. (Culver City, CA : Sony Pictures Home Entertainment, 2015)
In the near future, crime is patrolled by an oppressive mechanized police force. But now, the people are fighting back. When one police droid, Chappie, is stolen and given new programming, he becomes the first robot with the ability to think and feel for himself. As powerful, destructive forces start to see Chappie as a danger to mankind and order, they will stop at nothing to maintain the status quo and ensure that Chappie is the last of his kind.
DVD release of the 2015 motion picture.
Special features: We are Tetravaal; Previews.
Director of photography, Trent Opaloch ; production designer, Jules Cook ; editors, Julian Clarke, Mark Goldblatt ; music by Hans Zimmer.
Sharlto Copley, Dev Patel, Ninja and Yo-Landi Visser, Jose Pablo Cantillo, Brandon Auret, Sigourney Weaver, Hugh Jackman.
MPAA rating: R; for violence, language and brief nudity.
DVD, region 1, anamorphic widescreen (2.40:1) presentation ; Dolby digital 5.1 surround.
Keywords: Robots -- Drama; Artificial intelligence -- Drama; Police -- Drama; Crime -- Drama; Artificial intelligence; Crime; Police; Robots; Science fiction films; Action and adventure films; Feature films; Fiction films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Action and adventure films; Drama; Feature films; Fiction films; Science fiction films; Thrillers (Motion pictures); Video recordings for people with visual disabilities; Video recordings for the hearing impaired